Buprenorphine for Cancer Pain: Results from a Systematic Review - Silveira, Maria; Powell, Victoria (Journal of Opioid Management, 2024)
Background: Buprenorphine may be safer and better-tolerated than full mu opioid receptor (MOR) agonists. Whether it effectively controls cancer-related pain is unclear. A prior review (Cochrane 2015) did not support prioritizing buprenorphine over full MOR agonists for cancer-associated pain. Purpose/hypothesis: We conducted an updated systematic review of buprenorphine’s effect on cancer-related pain including both new studies and additional study designs Procedures/data/observations: We searched Cochrane, OVID Medline, EMBASE, EBSCO and Web of Science for studies published in any language up to May 2023 for studies that examined buprenorphine’s impact upon pain severity/intensity in patients with active cancer. Risk of bias and study quality were assessed using the Cochrane Collaboration tool for randomized controlled trials (RCTs), and the Newcastle-Ottawa Scale for cohort and case-control studies. Data were synthesized using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Conclusions/applications: 2322 publications were identified and 42 studies were included (14 RCTs , 10 pre-post uncontrolled, 5 cohort, and 2 case-control studies). All had moderate-high risk of bias. One RCT showed buprenorphine was superior to placebo. 11 RCTs (12 papers) showed buprenorphine was as effective as full MOR agonists for cancer pain. 10-30 percent of cancer patients trialing buprenorphine did not achieve adequate response.